Influence of increased sliding speed on the structure and properties of piston rings with ion-plasma coating - Skoblo, T.S.; Sidashenko, A.I.; Garkusha, I.E.; Taran, A.V.; Muratov, R.M.; Maltsev, Т.V. (Вопросы атомной науки и техники, 2018)
The technology of ion-plasma hardening of oil-scraper piston rings of D100 diesel engine by multilayer TiN/CrN composition is proposed. Comparative tests for friction and wear of the piston rings have been carried out and the multiple increasing in wear resistance of the rings with ion-plasma coating is shown. An estimation of the change in their microhardness before and after the tests was performed. The nature of the change in the composition of coatings: both in the initial state and during operation by local micro-X-ray spectral analysis was established. A method for estimating the effective thickness of coatings, which is protected by a patent, is proposed.